2011
DOI: 10.3233/jae-2011-1371
|View full text |Cite
|
Sign up to set email alerts
|

Compressive and tensile stresses of magnetorheological fluids in squeeze mode

Abstract: Magnetorheological (MR) fluid exhibits a perceptible change of rheological properties in reaction to external magnetic field. The MR fluids are currently enjoying renewed interest within the technical community in terms of the fundamental and applied research. MR fluids behaviour in squeeze mode is one of the areas that remain unknown as compared to valve and shear modes. Therefore, this paper presents stress-strain relationships of MR fluids under compression and tension tests. The results demonstrated that M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Despite of the fact the length of each shear effective area were the same, the three coils which provide the magnetic flux density, have distinct configurations. Moreover, the magnitude of flux density in these simulation results were in a good range based on the available data supplied by Lord Corporation and other researchers (Mazlan et al 2009;El Wahed and McEwan 2011;Mazlan et al 2011;Wang et al 2011). From the values of average magnetic flux density obtained, the values of yield stress can be estimated by applying the approximate polynomial equation for MRF-132DG constructed by Nguyen et al (2008…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Despite of the fact the length of each shear effective area were the same, the three coils which provide the magnetic flux density, have distinct configurations. Moreover, the magnitude of flux density in these simulation results were in a good range based on the available data supplied by Lord Corporation and other researchers (Mazlan et al 2009;El Wahed and McEwan 2011;Mazlan et al 2011;Wang et al 2011). From the values of average magnetic flux density obtained, the values of yield stress can be estimated by applying the approximate polynomial equation for MRF-132DG constructed by Nguyen et al (2008…”
Section: Resultssupporting
confidence: 63%
“…The typical properties of both MR fluids are summarized in Table 1. These commercial MR fluids were also used by other researchers in their studies (Goncalves and Carlson 2009;Mazlan et al 2011) while some researchers preferred to utilize a home-made MR fluids (Genc and Phule 2002; El Wahed and McEwan 2011).…”
Section: Mr Fluidmentioning
confidence: 99%
“…This model has been effectively used in several applications and theoretical analyses, including (Gavin, 2001;Mazlan, 2008). When the yield stress (dependent on the magnetic field strength) is exceeded, the MR fluid begins to yield.…”
Section: Mrfluid Modelmentioning
confidence: 99%
“…Vieira et al (2003) studied the influences of magnetic field intensity, frequency, and amplitude on the characteristics of MRF squeeze flow. Mazlan et al (2007Mazlan et al ( , 2008aMazlan et al ( , 2008bMazlan et al ( , 2009Mazlan et al ( , 2011 further revealed the effects of squeeze velocity, squeeze gap, and current intensity. Zhang et al (2011) studied the MRF dynamic behaviors up to 50 Hz.…”
Section: Introductionmentioning
confidence: 96%